2007
DOI: 10.1101/gad.1580407
|View full text |Cite
|
Sign up to set email alerts
|

Reinduction of ErbB2 in astrocytes promotes radial glial progenitor identity in adult cerebral cortex

Abstract: Radial glial cells play a critical role in the construction of mammalian brain by functioning as a source of new neurons and by providing a scaffold for radial migration of new neurons to their target locations. Radial glia transform into astrocytes at the end of embryonic development. Strategies to promote functional recovery in the injured adult brain depend on the generation of new neurons and the appropriate guidance of these neurons to where they are needed, two critical functions of radial glia. Thus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 86 publications
3
45
0
1
Order By: Relevance
“…60,61 Other groups demonstrated that mature astrocytes locally resume proliferation and dedifferentiate in response to brain injury and other stimuli. 57,62 Thus, both scenarios can occur. In our study, nestin-positive reactive astrocytes were observed very early during cancer cell invasion of the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…60,61 Other groups demonstrated that mature astrocytes locally resume proliferation and dedifferentiate in response to brain injury and other stimuli. 57,62 Thus, both scenarios can occur. In our study, nestin-positive reactive astrocytes were observed very early during cancer cell invasion of the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Radial glia maintenance and/or differentiation results from a balance between neurogenic and stem cell-maintaining molecules such as neuregulin-1 and Notch1 [14,15,16,17,73,74,75,76,77,78,79], and differentiating molecules such as TGF-β 1 [26,80], cardiotrophin [25] and ciliary neurotrophic factor [18], which are crucial to control the correct timing of the neurogenic-to-gliogenic switch of radial glia cells. …”
Section: Discussionmentioning
confidence: 99%
“…For cell transplantation studies, FoxJ1 -/-EGFP or FoxJ1 +/+EGFP cells were injected into the lateral ventricles of wild-type and FoxJ1-null animals using a stereotaxic apparatus. Cell preparations were obtained using fluorescence-activated cell sorting (Dako Cytomation MoFlo; NCSU Flow Cytometry and Cell Sorting Laboratory), followed by resuspension in artificial cerebrospinal fluid (Ghashghaei et al, 2007b) supplemented with 10 ng of epidermal growth factor (Egf) and fibroblast growth factor (Fgf2) to a final concentration of 1 ϫ 10 6 EGFP + cells/l. For both transplantation and lentiviral injections, newborn pups (P0) were anesthetized by means of hypothermia as described previously (Ghashghaei et al, 2007b).…”
Section: Intraventricular Lentiviral and Cell Injectionsmentioning
confidence: 99%
“…Cell preparations were obtained using fluorescence-activated cell sorting (Dako Cytomation MoFlo; NCSU Flow Cytometry and Cell Sorting Laboratory), followed by resuspension in artificial cerebrospinal fluid (Ghashghaei et al, 2007b) supplemented with 10 ng of epidermal growth factor (Egf) and fibroblast growth factor (Fgf2) to a final concentration of 1 ϫ 10 6 EGFP + cells/l. For both transplantation and lentiviral injections, newborn pups (P0) were anesthetized by means of hypothermia as described previously (Ghashghaei et al, 2007b). For shFoxJ1-lenti and control-lenti vector injections, 1 l of each vector (10 10 infectious units/ml) was injected into the anterior lateral ventricles of P0 pups using stereotaxic surgery (n3 per construct …”
Section: Intraventricular Lentiviral and Cell Injectionsmentioning
confidence: 99%